Performance of M-Ary Pulse Position Modulated Optical Wireless Communications Systems in the Marine Atmosphere - Baykal, Yahya; Ata, Yalcin; Gokce, Muhsin C. (Optical Soc Amer, 2021)
The marine atmosphere exhibits different turbulence spectrum characteristics when compared to the turbulence spectra of the land atmosphere and underwater medium. The performance of M-ary pulse position modulated (PPM) optical wireless communications (OWC) systems operating in the marine atmosphere, as measured by the bit error rate (BER), is studied here. In our investigation, the scintillation index and the average intensity in marine atmospheric turbulence are used. The variations of BER performance are reported against the marine atmospheric turbulence parameters for various values of the average current gain of the avalanche photodetector (APD), data bit rate of theOWClink, and M value of the M-ary PPM. (C) 2021 Optical Society of America
Performance of M-ary pulse position modulated optical wireless communications systems in the marine atmosphere
Gokce, Muhsin Caner/0000-0003-4465-1983; Baykal, Yahya/0000-0002-4897-0474